PELAKSANAAN PROMOSI MELALUI MEDIA SOSIAL DI SWISS-BELHOTEL HARBOUR BAY BATAM PROVINSI KEPULAUAN RIAU - Shela Nursanti; Firdaus Yusrizal (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The promotion is part of the marketing activities i.e. convince, persuade, inform, explain, and remind the product either goods or services. The implementation of the promotion done by making the product more attractive to the hotel and is known by the prospective customer, so that they are more interested in stay or buy other products. This research uses descriptive quantitative methods to address the problem. For research purposes, first used the technique of triangulation, and for the purpose of both a descriptive statistical techniques used. The samples in the were 120 respondents, who were teken by using stratified random sample. While data collection techniques in the study use observation, interviews, and questionnaires. The results of the research implementation of Promotion through Social Media in Swiss-Belhotel Harbour Bay Batam Province of Riau Islands is the maintainer uses 2 types of social media i.e. facebook fanspage and instagram. Promotional mix or sub-variable on the promotion through the media soisal divided into advertising and public relations. Overall, the responses of the respondents against the implementation of promotion through social media conducted by the Swiss-Belhotel Harbour Bay Batam has done well.Keywords: Social Media, public relations, advertising, promotions